Hollywood’s most reliable audience. Il pubblico adolescente tra consumo, narrazioni e partecipazione (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
This paper aims to analyse the role of the “teen audience” in the process of definition and evolution of the “teen movie” genre. Since its origin, in fact, this genre is presented as the result of the interaction between public and industry, between production and consumption practices. Today, in the era of convergence culture, the “teen movie” strengthens the relationship with its audience through new forms of participation. This allows us to analyse both the needs for building a community typical of fandom practices, and the dynamics of identity construction and identification expressed by the “digital generation”.